Ultra-Wide Band (10 GHz Bandwidth) Microstrip Patch Antenna for Millimeter Wave - 5G Applications - Ur Rehman, Tauseef; Muqarrab, Nabeel (International Journal of Advanced Engineering, Management and Science, 2022)
This paper introduces a microstrip patch antenna (MPA) for fifth Generation (5G)/ millimeter-Wave (mm-Wave) applications for frequencies > 50 GHz. The proposed antenna is designed and simulated on a flexible substrate of cotton jean having εr =1.76, δ =0.078, and a height of 1 mm. The designed antenna operates over an impedance bandwidth of 10 GHz with a maximum gain of 6.167 dBi. The antenna patch's largest dimension is 2.82mm (0.52687 λ) and the ground is 8 mm (1.499 λ), whereas λ is calculated at the center frequency of impedance bandwidth.